1998
DOI: 10.1002/(sici)1521-4141(199812)28:12<4149::aid-immu4149>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Similar as well as distinct MHC class I-binding peptides are generated by exogenous and endogenous processing of hepatitis B virus surface antigen

Abstract: Murine MHC class I-restricted cytotoxic T lymphocyte (CTL) responses can be primed by exogenous as well as endogenous hepatitis B surface antigen (HBsAg). Immunodominant CTL-defined epitopes of this viral envelope protein are the L d-binding 12-mer S28-39 pep-tide IPQSLDSWWTSL in H-2 d mice, and the K b-binding 8-mer S208-215 peptide ILSPFLPL in H-2 b mice. We tested if CTL recognizing these epitopes can be primed in vivo by HBsAg delivered as either an exogenous antigen (native HBsAg lipoprotein particles), o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 32 publications
2
61
0
Order By: Relevance
“…It has been shown that in an inflammatory condition the constitutive proteasome is modified into immunoproteasome and that the epitope processing could be affected by either favoring or dampening epitope production (52). In addition, an alternative processing pathway is available for specific CTL induction by HBsAg, since exogenous envelope Ag can also enter the class I processing pathway and induce class I-restricted CTL (53,54). It was also shown that the alternative exogenous or the classical endogenous pathway may generate different peptides in mice (54).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that in an inflammatory condition the constitutive proteasome is modified into immunoproteasome and that the epitope processing could be affected by either favoring or dampening epitope production (52). In addition, an alternative processing pathway is available for specific CTL induction by HBsAg, since exogenous envelope Ag can also enter the class I processing pathway and induce class I-restricted CTL (53,54). It was also shown that the alternative exogenous or the classical endogenous pathway may generate different peptides in mice (54).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an alternative processing pathway is available for specific CTL induction by HBsAg, since exogenous envelope Ag can also enter the class I processing pathway and induce class I-restricted CTL (53,54). It was also shown that the alternative exogenous or the classical endogenous pathway may generate different peptides in mice (54). The processing of HBsAg secreted following natural infection or produced after DNA-based immunization could thus result in slightly different sets of epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, H-2 d mastocytome cells p815 were pulsed for 1 h at 37 ° C, 5% CO 2 in complete medium with 10 mmol/L S (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) peptide IPQSLDSWWTSL from HBsAg. 33 After incubation p815 cells were further incubated for another 15 min with Mitomycin C (Sigma). The cells were extensively washed to avoid any trace of Mitomycin C and resuspended in complete medium for counting.…”
Section: Preparation Of Target and Effector Cellsmentioning
confidence: 99%
“…After washing, the cells were counted and distributed at 2 × 10 6 cells/mL in 10 mL RPMI FCS in 25 cm 2 flasks (Nalge-Nunc, Rochester, NY, USA) and stimulated with 10 mg/mL of peptide S (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) . After culturing for 4 days in 5% CO 2 , half of the total medium was substituted and new medium containing 2 × 10 4 U/mL of IL-2 was added.…”
Section: In Vitro Re-stimulation Of Primed Ctlmentioning
confidence: 99%
“…Specific cytolytic activity of cells was tested in short-term 51 Cr-release assays against RBL5, RBL5/BMG (transfected with the BMGneo vector without insert), or RBL5/S transfectants (carrying the HBsAg-encoding BMGneo vector) (23). After a 3.5-h incubation at 37°C, 50 l of supernatant was collected for gamma-radiation counting.…”
Section: Hbsag-specific Ctlmentioning
confidence: 99%